Maize (Zea mays L.) Seedlings Rhizosphere Microbial Community as Responded to Acidic Biochar Amendment Under Saline Conditions - Soothar, Mukesh Kumar; Hamani, Abdoul Kader Mounkaila; Sardar, Muhammad Fahad; Sootahar, Mahendar Kumar; Fu, Yuanyuan; Rahim, Riffat; Soothar, Jay Kumar; Bhatti, Saleem Maseeh; Abubakar, Sunusi Amin; Gao, Yang; Sun, Jingsheng (Frontiers in Microbiology, 2021)
Biochar has extensively been used for multiple purposes in agriculture, including improving soil microbial biomass. The current study aimed to investigate the effect of acidic biochar on maize seedlings rhizosphere bacterial abundance under salinity. There were seven treatments and three replicates in a controlled greenhouse coded as: B0S1, B1S1 and B2S1 and B0S2, B1S2 and B2S2. CK is control (free of biochar and salt), B0, B1 and B2 are 0, 15 and 30 g biochar (kg soil)-1, and S1 and S2 are 0.5 and 1 g salt pot-1 were amended, respectively. After harvesting the maize seedlings, the soil samples were collected and analyzed for soil microbial biomass, bacterial abundance, and diversity. The results revealed that relative abundance of Proteobacteria, Actinobacteria and Chloroflexi increased on phylum level, while Actinomarinales, Alphaprobacteria and Streptomyces enhanced on genus level respectively in B2S1 and B2S2, when compared to CK and non-biochar amended soil under saline conditions. The relative abundance of Actinomarinales was positively correlated with total potassium (TK) and Gematimonadetes negatively correlated with total phosphorus (TP). Biochar addition slightly altered the Ace1, Chao1, and alpha diversity. Principal component analysis (PCA) responded the changes in soil bacterial community were closely associated with biochar when compared to CK and salt treated soils. In conclusion, acidic biochar showed improved soil microbial community under salinity.